Human Papillomavirus infection: discussion of a clinical case in gynaecological cytology - Eliseu, C; I, Murça; V, Sousa; P, Agapito (Citotech Online - Case Review, 2023)
Human Papilloma Virus infections are a public health problem worldwide. Annually, and associated with cervical cancer, persistent infections by oncogenic strains are responsible for millions of pre-neoplastic and neoplastic lesions in women. Cytology plays a fundamental role in identifying these lesions, since both conventional smears and liquid-base cytology exams stand as an essential preventive measure. In addition to their low cost and easy access, these tests allow the detection of pre-neoplastic lesions in asymptomatic women, so that they can receive adequate treatment and prevent the lesions from progressing to cancer. However, the attribution of a cytological diagnosis is not always simple, and differentials must be considered by the cytologist to avoid misinterpretation. This article presents a clinical case of a 70-year-old woman who underwent a conventional cervical-vaginal smear and in which it was possible to observe an atrophic epithelium with the presence of atypical cells. This type of epithelium can make differential diagnosis with cervical lesions, namely with high-grade intraepithelial lesion (HSIL), therefore, it is important to identify and discuss the cytomorphological characteristics used for attribution of the cytological result.